2023
DOI: 10.56556/jescae.v2i4.602
|View full text |Cite
|
Sign up to set email alerts
|

A review of tropical blue carbon ecosystems for climate change mitigation

Asif Raihan

Abstract: Tropical blue carbon ecosystems encompass several components such as mangroves, seaweed, and seagrass, which play a crucial role in delivering a diverse array of services including regulation, provisioning, cultural, and support functions to a significant human population. The preservation and rehabilitation of tropical marine ecosystems hold significant importance for society due to the adverse consequences associated with their degradation, which include the impairment of crucial services such as coastal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The present study employed the systematic literature review methodology as suggested by Tawfik et al (2019). The systematic literature review framework is considered to be a dependable approach (Benita, 2021;Raihan & Bijoy, 2023;Raihan & Himu, 2023;Raihan, 2023e;2023f;2023g). A preliminary review of the literature was conducted to identify pertinent articles, validate the proposed idea, avoid redundancy with previously covered issues, and ensure the availability of sufficient articles for conducting a comprehensive analysis of the subject matter.…”
Section: Methodsmentioning
confidence: 99%
“…The present study employed the systematic literature review methodology as suggested by Tawfik et al (2019). The systematic literature review framework is considered to be a dependable approach (Benita, 2021;Raihan & Bijoy, 2023;Raihan & Himu, 2023;Raihan, 2023e;2023f;2023g). A preliminary review of the literature was conducted to identify pertinent articles, validate the proposed idea, avoid redundancy with previously covered issues, and ensure the availability of sufficient articles for conducting a comprehensive analysis of the subject matter.…”
Section: Methodsmentioning
confidence: 99%
“…Regrettably, forests are confronted with numerous issues. Worldwide, forests are experiencing swift deterioration as a result of the exploitation for timber, development of agriculture, and urbanization [25] . The effects of climate change, such as wildfires, are exacerbating the process of worldwide forest degradation [26] .…”
Section: Article Infomentioning
confidence: 99%